2016
DOI: 10.17129/botsci.627
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatology and ecophysiology of the urban vegetation of a city with tropical climate modified by altitude in Mexico

Abstract: Background. Environmental conditions in edges of vegetation fragments affect life cycle characteristics of the native biota (edge effect). We evaluated the edge effect on two Bursera species, which are representative of the mature community of the tropical deciduous forest (TDF) in Mexico. Hypothesis. We expected a population structure reflecting the affectation to reproduction, survival and growth in the edges of TDF fragments. Studied species. Bursera fagaroides, B. palmeri. Study site and years of study. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This response showed a higher g S sensitivity to VPD and ψ compared to T A and PAR. Differences in stomatal sensitivity found here may be caused by different microclimates at each study site, which could cause acclimatization of stomata to the urban environment (Barradas et al, 2016). Stomatal responsiveness could also be an adaptation (i.e., protective of water loss) related to different management practices (e.g., irrigation) at each site.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…This response showed a higher g S sensitivity to VPD and ψ compared to T A and PAR. Differences in stomatal sensitivity found here may be caused by different microclimates at each study site, which could cause acclimatization of stomata to the urban environment (Barradas et al, 2016). Stomatal responsiveness could also be an adaptation (i.e., protective of water loss) related to different management practices (e.g., irrigation) at each site.…”
Section: Discussionmentioning
confidence: 81%
“…It is worth noting that P. alba had a better g S performance than P. deltoides, showing that other factors rather than phylogeny, may improve species performance, such as plasticity and climate of origin (Nicotra and Davidson, 2010;Du et al, 2019). However, studies in tropical areas showed that phenomenological models, such as the boundary line analysis, are site-specific (Barradas et al, 2004). Also, for the multiplicative model, we used input data derived from meteorological stations from Mexico City; a different approach might be using modeled meteorological data (e.g., PRISM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…protected slopes and gulleys). Furthermore, microclimate can alter species’ ecophysiology and thus their ability to cope with climate change (Barradas, Ruiz‐Cordova, & Esperón‐Rodríguez, ). Whenever possible, a more detailed climate assessment considering local microclimate should be used to develop urban planning and management actions.…”
Section: Discussionmentioning
confidence: 99%